2012
DOI: 10.1021/ja305903u
|View full text |Cite
|
Sign up to set email alerts
|

Facile, Solution-Based Synthesis of Soft, Nanoscale Janus Particles with Tunable Janus Balance

Abstract: We present a novel, versatile, and simple solution-based routine to produce soft, nanosized Janus particles with tunable structural and physical properties at high volume yield. This process is based on the cross-linking of compartments within precisely defined multicompartment micelles (MCMs), which are themselves formed by the self-assembly of ABC triblock terpolymers. Therein, the C blocks form the stabilizing corona emanating from B compartments, which in turn reside on an A core. Cross-linking of the B co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
224
0
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 249 publications
(234 citation statements)
references
References 72 publications
5
224
0
5
Order By: Relevance
“…Firstly, the cooperative assembly behavior and the possible fusion of two types of nanoparticles were investigated to exam the formation of different compartments in the hydrogel formulation. Our previous study and other reports on multicompartment micelles have demonstrated that immiscible hydrocarbons and fluorocarbons were inclined to microphase separation and form their own compartments in the micellar core, which was usually observed by transmission electron microscope (TEM) [38,51]. As to this aspect, the FRET technology was utilized to investigate the incompatible property of selected nanoparticles, which might result in the multicompartment hydrogel formation.…”
Section: Preparation and Characterization Of Combination Drug Encapsumentioning
confidence: 98%
See 1 more Smart Citation
“…Firstly, the cooperative assembly behavior and the possible fusion of two types of nanoparticles were investigated to exam the formation of different compartments in the hydrogel formulation. Our previous study and other reports on multicompartment micelles have demonstrated that immiscible hydrocarbons and fluorocarbons were inclined to microphase separation and form their own compartments in the micellar core, which was usually observed by transmission electron microscope (TEM) [38,51]. As to this aspect, the FRET technology was utilized to investigate the incompatible property of selected nanoparticles, which might result in the multicompartment hydrogel formation.…”
Section: Preparation and Characterization Of Combination Drug Encapsumentioning
confidence: 98%
“…Among these vectors, multicompartment release systems [30][31][32][33][34][35][36] have emerged in recent years as an ideal platform for simultaneous encapsulation of multiple drugs in segregated compartments. However, until now, much effort has been paid to develop multicompartment structures [34,[37][38][39][40][41][42][43] and few such systems could easily succeed in selective encapsulation and controlled release of multiple drugs. One hiding barrier is that the encapsulation demands precise chemical structure adjustment or advanced technologies, especially for separate drug encapsulation.…”
Section: Introductionmentioning
confidence: 99%
“…The corona ratio can be tuned by altering the block ratios of the polymers. 58,59 This method has been used to form…”
Section: Block Copolymer Nanomachinesmentioning
confidence: 99%
“…On the basis of the study of British scholar Bangham [1] , normal vesicles have many applications in biomimicry [2] , biopharmaceutics [3] , nanoparticles synthesis [4] . As the counterparts of normal vesicles, reverse vesicles are formed in organic, nonpolar solvents ("oils") [5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%